Preoperative Evaluation Clinic Visit Is Associated with Decreased Risk of In-hospital Postoperative Mortality. (August 2016) - Blitz, Jeanna D.; Kendale, Samir M.; Jain, Sudheer K.; Cuff, Germaine E.; Kim, Jung T.; Rosenberg, Andrew D.
Abstract : Background: As specialists in perioperative medicine, anesthesiologists are well equipped to design and oversee the preoperative patient preparation process; however, the impact of an anesthesiologist-led preoperative evaluation clinic (PEC) on clinical outcomes has yet to be fully elucidated. The authors compared the incidence of in-hospital postoperative mortality in patients who had been evaluated in their institution's PEC before elective surgery to the incidence in patients who had elective surgery without being seen in the PEC. Methods: A retrospective review of an administrative database was performed. There were 46 deaths from 64, 418 patients (0.07%): 22 from 35, 535 patients (0.06%) seen in PEC and 24 from 28, 883 patients (0.08%) not seen in PEC. After propensity score matching, there were 13, 964 patients within each matched set; there were 34 deaths (0.1%). There were 11 deaths from 13, 964 (0.08%) patients seen in PEC and 23 deaths from 13, 964 (0.16%) patients not seen in PEC. A subanalysis to assess the effect of a PEC visit on deaths as a result of failure to rescue (FTR) was also performed. Results: A visit to PEC was associated with a reduction in mortality (odds ratio, 0.48; 95% CI, 0.22 to 0.96, P = 0.04) by comparison of the matched cohorts. The FTR subanalysis suggested that the proportion of deaths attributable to an unanticipated surgical complication was not significantly different between the two groups ( P = 0.141). Conclusions: An in-person assessment at the PEC was associated with a reduction in in-hospital mortality. It was difficult to draw conclusions about whether a difference exists in the proportion of FTR deaths between the two cohorts due to small sample size. Abstract : An in-person assessment in an anesthesiologist-led preoperative evaluation clinic was associated with a reduction in in-hospital mortality.